Effects of Diazepam on Reaction Times to Stop and Go - Sarkar, Swagata; Choudhury, Supriyo; Islam, Nazrul; Chowdhury, Mohammad Shah Jahirul Hoque; Chowdhury, Md Tauhidul Islam; Baker, Mark R.; Baker, Stuart N.; Kumar, Hrishikesh (Frontiers in Human Neuroscience, 2020)
Introduction: The ability to stop the execution of a movement in response to an external cue requires intact executive function. The effect of psychotropic drugs on movement inhibition is largely unknown. Movement stopping can be estimated by the Stop Signal Reaction Time (SSRT). In a recent publication, we validated an improved measure of SSRT (optimum combination SSRT, ocSSRT). Here we explored how diazepam, which enhances transmission at GABAA receptors, affects ocSSRT. Methods: Nine healthy individuals were randomized to receive placebo, 5 mg or 10 mg doses of diazepam. Each participant received both the dosage of drug and placebo orally on separate days with adequate washout. The ocSSRT and simple reaction time (RT) were estimated through a stop-signal task delivered via a battery-operated box incorporating green (Go) and red (Stop) light-emitting diodes. The task was performed just before and 1 h after dosing. Result: The mean change in ocSSRT after 10 mg diazepam was significantly higher (+27 ms) than for placebo (−1 ms; p = 0.012). By contrast, the mean change in simple response time remained comparable in all three dosing groups (p = 0.419). Conclusion: Our results confirm that a single therapeutic adult dose of diazepam can alter motor inhibition in drug naïve healthy individuals. The selective effect of diazepam on ocSSRT but not simple RT suggests that GABAergic neurons may play a critical role in movement-stopping.